Implementation Of Development And Registration And Elimination Acceptances Of Rights Based On Law Number 4 Year 1996 Regarding Rights Of Responsibility - Yunimar Yunimar (Fakultas Sastra Universitas Ekasakti, 2017)
Mortgage right are the security rights imposed on land rights. On April 9, 1996, Law Number 4 of 1996 was enacted on the Land and Property Rights related to the land, or more briefly referred to as UUHT (Law on Mortgage Rights). UUHT seeks to provide legal certainty and protection to all parties in utilizing the land as an object of Mortgage Rights.